Determinants of utilisation of traditional birth attendant services by pregnant women in Ogbomoso, Nigeria - T., Awotunde O.; T. A., Awotunde; F. O., Fehintola; Adesina S. A., Adesina; O. A., Oladeji; A. O., Fehintola; D. E., Ajala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was designed to assess the determinants of utilization of Traditional Birth Attendants (TBAs) services by pregnant women in different communities in Ogbomoso, Nigeria. Methods: This was a community- based cross-sectional study. Fisher’s formula was used to calculate the sample size and a total of 270 eligible pregnant women were enrolled for the study using multistage sampling technique. Data was collected using pretested structured interviewer-administered questionnaire. Data analysis was done using SPSS version 20 and results were presented in frequencies and percentages. Results: Factors found to have a significant influence on the utilization of TBA services in this study include: low educational status (p <0.001), lower socioeconomic status (p <0.001), and compassionate care given by the TBAs (p=0.004). Other factors include service proximity and lower cost of TBA services. Conclusions: The impact of TBAs and their services cannot be overemphasized in the present state of maternal and child health in Nigeria. Lower educational status among others has been found to be a strong predictor of utilization of TBA services. There is, therefore, the need to improve the educational and socioeconomic status of women in order to allow them to access quality health care services that will safeguard their well-being. Inculcating compassionate care into orthodox healthcare delivery will go a long way to improve patronage and discourage TBA utilization.